ANALYSIS OF TEACHING READINESS OF FKIP STUDENTS OF TEACHER EDUCATION STUDY PROGRAM, RIAU UNIVERSITY CLASS OF 2018 - Siska Indriani (Yayasan Thaifah Manshurah Pekanbaru, 2022)
This study aims to determine and describe the teaching readiness of Elementary School Teacher Education Students of Riau University Class of 2018. This research will be carried out in the Elementary School Teacher Education Study Program at the Faculty of Teacher Training and Education, University of Riau. This research was conducted in November-December 2021. This research is a quantitative descriptive study. The method used in this study was a survey with data collection techniques using questionnaires. The population in this study was all FKIP students of Riau University, PGSD Study Program class of 2018. The results showed that the overall results of the indicators studied showed that students of the PGSD study program at Riau University had physical readiness, mental readiness, and the ability and skills in teaching had met the minimum standards required as an educator.